Ultrasonographic Nomograms of Foetal Fourth Ventricle Biometry and its Correlation with Transcerebellar Diameter and Gestational Age among Normal Foetuses: A Cross-sectional Study - N Padmalatha; Paarthipan; Parthasarathy; Francis Nanda Prakash Monteiro (Journal of Clinical and Diagnostic Research, 2025)
Introduction: The foetal fourth ventricle marks an important landmark for evaluating the development of the posterior fossa. Prenatal diagnosis of midbrain and hindbrain abnormalities is based on aberrant cerebellum and retrocerebellar space size and shape, with the most prevalent sign being an ‘open fourth ventricle’. Aim: To present the normal range of measurements of the foetal fourth ventricle and correlate the fourth ventricle biometry with Transcerebellar Diameter (TCD) and Gestational Age (GA) in normal foetuses. Materials and Methods: This cross-sectional study included 260 pregnant women with low-risk pregnancies between 19 and 35 weeks of gestation, with the known Last Menstrual Period (LMP) confirmed by first trimester ultrasonography. The foetal heads were scanned in the axial plane. The TCD and fourth ventricle anteroposterior and transverse diameters were obtained ultrasonographically from the pregnant women who were recruited to the Department of Radiology, Rajarajeswari Medical College and Hospital, Bengaluru, India, between January 2021 and December 2023. The routine foetal biometric parameters, such as Biparietal Diameter (BPD), Head Circumference (HC), Abdominal Circumference (AC), and Estimated Foetal Birth Weight (EFBW), were also recorded. Pearson correlation coefficients were calculated to examine the strength of the linear relationship between each of the fourth ventricle parameters, GA, and TCD. Regression analysis was performed to determine the equation of the linear fitted function with each of the independent variables (GA, TCD). All statistical analyses were performed using Statistical Package for Social Sciences (SPSS) software, Version 22.0 (IBM, Armonk, New York). Results: The mean and Standard Deviation (SD) of the fourth ventricle anteroposterior and transverse diameters are 2.122 mm (SD=0.309) and 5.648 mm (SD=1.975), respectively. The Pearson correlation coefficients of the fourth ventricle anteroposterior diameter for GA and TCD were r=0.917 and r=0.931, respectively. The coefficients of the fourth ventricle transverse diameter for GA and TCD were r=0.869 and r=0.884, respectively (p<0.001). The regression equations were plotted between GA and fourth ventricle anteroposterior diameter (r=0.917; p<0.001; y=0.406+(0.0716×GA (weeks) and transverse diameter (r=0.869; p<0.001; y=-4.753+(0.434×GA in weeks. A linear regression line was also plotted between TCD and fourth ventricle anteroposterior diameter (r=0.931; p<0.001; y=0.783 + (0.0511×TCD (mm) and transverse diameter (r=0.884; p<0.001; y=-2.483+(0.310×TCD in mm. Conclusion: The study established normal foetal fourth ventricle measurements and found strong correlations between GA and TCD. These results support their use as reliable markers of normal foetal brain development.